2015
DOI: 10.1007/s10661-015-4600-9
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of rice field water with sulfonylurea and phenoxy herbicides in the Muda Irrigation Scheme, Kedah, Malaysia

Abstract: The purpose of the present study was to investigate the potential risk of herbicide contamination (2,4-dichlorophenoxy (2,4-D), 2-methyl-4-chlorophenoxyacetic acid (MCPA), metsulfuron, bensulfuron, and pyrazosulfuron) in the rice fields of the Muda Irrigation Scheme, Kedah, Malaysia. The study included two areas with different irrigation water sources namely non-recycled (N-RCL) and recycled (RCL) water. Periodic water sampling was carried out from the drainage canals during the planting period of the wet seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The adsorbent eluents are usually organic solvents containing appropriate concentrations of buffer solution or aqueous solution for the reverse phase column. The adsorbent eluents for anion-exchange are usually ionic compounds (Ismail et al 2015d). In the experiment, Cromabond PS-H + /OH -was washed with 3 mL AcOH/water (5:95, v/v) for the removal of impurities.…”
Section: Results and Discussion Ph Of Samplesmentioning
confidence: 99%
“…The adsorbent eluents are usually organic solvents containing appropriate concentrations of buffer solution or aqueous solution for the reverse phase column. The adsorbent eluents for anion-exchange are usually ionic compounds (Ismail et al 2015d). In the experiment, Cromabond PS-H + /OH -was washed with 3 mL AcOH/water (5:95, v/v) for the removal of impurities.…”
Section: Results and Discussion Ph Of Samplesmentioning
confidence: 99%
“…Previous studies have demonstrated that FIGURE 1. GC-XSD Chromatograms of (a) Chlorpyrifos standard solution, 0.02 μg/mL, (b) Untreated sample of soil and (c) Spike soil sample containing 0.02 μg/g of chloropyrifos several factors, such as adsorption of the pesticide to soil particles, water solubility of the pesticide, volume of leachate, pH and soil texture, can influence the leaching of the pesticides through the soil (Ismail et al 2015d;Nicholls et al 1982). Other factors such as volatilization, runoff, leaching, chemical and biological degradation, absorption and photolysis could enhance the degradation rate especially under the Malaysian weather conditions.…”
Section: Results and Discussion Standard Calibration Curve And Recovementioning
confidence: 99%
“…Temperature has a significant effect on adsorption by soils through its effect on solubility, and this adsorption has been shown for parathion by Behrendt et al (1990) as well as for atrazine (Dinehart et al 2009;Ismail et al 2015d). Druart et al (2011) explored the dissimilarity in the adsorption mechanisms of the protonated and ionized forms of pentachlorophenol (PCP) by standardizing their adsorption coefficients at three different temperatures (4°C, 25°C and 55°C).…”
Section: Effect Of Temperature On Adsorptionmentioning
confidence: 94%